The Silk Road : Central Asia, Afghanistan and Iran : A Travel Companion - Tucker, Jonathan; Foreword by Theroux, Paul (London I.B. Tauris & Company Ltd., 2015)
Stretching from the ancient Chinese capital of Xian across the expanses of Central Asia to Rome, the Silk Road was, for 2,000 years, a vibrant network of arteries that carried the lifeblood of nations across the world. Along a multitude of routes everything was exchanged: exotic goods, art, knowledge, religion, philosophy, disease and war. From the East came silk, tea, jade, paper, procelain, spices and Buddhism; from the West, horses, weapons, lions, precious stones and cotton. From its earliest beginnings in the days of Alexander the Great and the Han Dynasty, the Silk Road expanded and evolved, reaching its peak under the Tang and Byzantine empires and gradually crumbling along with decline of the Mongol empire. In this beautifully-illustrated book, which covers the Central Asian section of the Silk Road - from Lake Issy Kul through Tashkent, Samarkand, Bukhara, the Kyzyl Kum Desert, Khiva and Merv to Herat, Kabul and Iran - Jonathan Tucker uses traveller's anecdotes and a wealth of literary and historical sources to celebrate the cultural heritage of the countries that lie along the Silk Road and illuminate the lives of those who once travelled through the very heart of the world.
Include Illustrations, Maps, Chronologies, Glossary, Notes, Bibliography and Index.
A Travel Companion.
Keywords: Trade routes -- Iran -- Asia, Central